A Mayor Regulación, Mayor Competencia: El Caso de la Interconexión en las Industrias de Electricidad y Telecomunicaciones - Quiroga, María del Rosario (Pontificia Universidad Católica del Perú, 2015)
El presente artículo describe la importancia de contar con un sistema regulatorio adecuado en el tema de la interconexión, a fin de tener una mayor competencia en los diferentes sectores de servicios. Así, a partir del caso en los sectores de electricidad y de telecomunicaciones, se verificará que, para el desarrollo de las respectivas industrias es necesario tener un marco normativo adecuado en el ámbito de la interconexión.

This article describes the need of ensure an adequate regulation system in the interconnection matter, looking for having an optimal competency on the different fields of service sectors. Thus, parting from the case of the electricity and telecommunications sectors, it will be verified that, for developing this industries it is necessary to have an adequate regulatory framework in interconnection matter.
Higher Regulation, Greater Competition: The Case of Interconnection in the Electricity and Telecommunications Industries
Keywords: Interconnection; Electricity Sector; Telecommunications Sector; Competency; Regulation; Interconexión; Sector electricidad; Sector telecomunicaciones; Competencia; Regulación; https://purl.org/pe-repo/ocde/ford#5.05.00